Limitations to the implementation of English language communicative skills teaching in rural Ugandan schools : a case study of Karamoja - Namusiginyi, Beatrice; Ørevik, Sigrid (African Perspectives of Research in Teaching & Learning (APORTAL), 2025)
Communicative skills teaching in English language has been widely recognized as an approach conducive to developing students' competence in academic as well as everyday use of English. However, its implementation in rural primary schools faces numerous challenges. This study was conducted in a remote area in Uganda to establish the limitations to the successful teaching of communicative skills in such a context. Using a qualitative approach combining interviews, document analysis and lesson observation, the study revealed limitations related to syllabus disconnect, inadequate teaching resources, cultural barriers, pedagogical practices, Mother-tongue policy and classroom environment. The findings in this study have implications for stakeholders in language teaching, teacher education and education policy in Uganda. It highlights the need to provide ongoing professional training to equip teachers of English language with innovative teaching approaches tailored to the learning conditions of learners in hard-to-reach areas.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 4, Volume 9, 2025
Keywords: English language teaching; Communicative skills teaching; Karamoja; English language -- Study and teaching; Karamojong language; English language -- Study and teaching (Elementary)